Best practice in primary care pathology: review 14. Issue 2 (6th September 2011) - Cabrera-Abreu, J C; Smellie, W S A; Bowley, R; Shaw, N
Abstract : This 14th best practice review is the second of a pair that examines tumour marker requesting primary care situations. This review considers carbohydrate antigen 125, α-fetoprotein and human chorionic gonadotropin. It is presented in question–answer format, referenced for each question. The recommendations represent a précis of guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents and evidence-based medicine reviews, supplemented by MEDLINE EMBASE searches to identify relevant primary research documents. They will be updated periodically to take into account new information.